19F MRI of the Lungs Using Inert Fluorinated Gases: Challenges and New Developments. Issue 2 (24th September 2018) - Couch, Marcus J.; Ball, Iain K.; Li, Tao; Fox, Matthew S.; Biman, Birubi; Albert, Mitchell S.
Abstract : Fluorine‐19 ( 19 F) MRI using inhaled inert fluorinated gases is an emerging technique that can provide functional images of the lungs. Inert fluorinated gases are nontoxic, abundant, relatively inexpensive, and the technique can be performed on any MRI scanner with broadband multinuclear imaging capabilities. Pulmonary 19 F MRI has been performed in animals, healthy human volunteers, and in patients with lung disease. In this review, the technical requirements of 19 F MRI are discussed, along with various imaging approaches used to optimize the image quality. Lung imaging is typically performed in humans using a gas mixture containing 79% perfluoropropane (PFP) or sulphur hexafluoride (SF6 ) and 21% oxygen. In lung diseases, such as asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis (CF), ventilation defects are apparent in regions that the inhaled gas cannot access. 19 F lung images are typically acquired in a single breath‐hold, or in a time‐resolved, multiple breath fashion. The former provides measurements of the ventilation defect percent (VDP), while the latter provides measurements of gas replacement (ie, fractional ventilation). Finally, preliminary comparisons with other functional lung imaging techniques are discussed, such as Fourier decomposition MRI and hyperpolarized gas MRI. Overall, functional 19 F lung MRI is expected to complement existing proton‐based structural imaging techniques, and the combination of structural and functional lung MRI will provide useful outcome measures in the future management of pulmonary diseases in the clinic. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:343–354.